Axonal cap‐dependent translation regulates presynaptic p35. Issue 3 (14th December 2013) - Hsiao, Kuangfu; Bozdagi, Ozlem; Benson, Deanna L.; Sotelo‐Silveira, José R.; Holt, Christine E.
ABSTRACT Axonal growth cones synthesize proteins during development and in response to injury in adult animals. Proteins locally translated in axons are used to generate appropriate responses to guidance cues, contribute to axon growth, and can serve as retrograde messengers. In addition to growth cones, mRNAs and translational machinery are also found along the lengths of axons where synapses form en passant, but contributions of intra‐axonal translation to developing synapses are poorly understood. Here, we engineered a subcellular‐targeting translational repressor to inhibit mRNA translation in axons, and we used this strategy to investigate presynaptic contributions of cap‐dependent protein translation to developing CNS synapses. Our data show that intra‐axonal mRNA translation restrains synaptic vesicle recycling pool size and that one target of this regulation is p35, a Cdk5 activating protein. Cdk5/p35 signaling regulates the size of vesicle recycling pools, p35 levels diminish when cap‐dependent translation is repressed, and restoring p35 levels rescues vesicle recycling pools from the effects of spatially targeted translation repression. Together our findings show that intra‐axonal synthesis of p35 is required for normal vesicle recycling in developing neurons, and that targeted translational repression provides a novel strategy to investigate extrasomal protein synthesis in neurons. © 2013 Wiley Periodicals, Inc. Develop Neurobiol 74: 351–364, 2014